2020
DOI: 10.1002/asjc.2407
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of dynamic interval type‐2 fuzzy control systems in frequency domain

Abstract: The present paper aims to analyze the stability of dynamic Interval Type-2 fuzzy control systems (IT2 FCSs) with adjustable parameters by investigating the existence of limit cycles based on the describing function (DF) method. To simplify the stability analysis, the following structured procedure is described. First, to avoid complex computation, a simple architecture of the IT2 FCS using two embedded Type-1 fuzzy control systems (T1 FCSs) is proposed. Then, the DF of IT2 FCS is obtained based on the DFs of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Takagi-Sugeno (T-S) fuzzy system has attracted abundant researchers' attention in last decades for its extraordinary ability to approximate nonlinearity at any precision through membership function connecting linear subsystems as in Takagi and Sugeno [1], allowing existing linear system theories [2][3][4][5] to be applied to nonlinearity system analysis. The failure to tackle membership function (MF) uncertainty for type-1 fuzzy set, on the other hand, necessitates a greater focus on interval type-2 (IT2) fuzzy model, which captures uncertainties via upper and lower MFs [6][7][8][9][10][11]. It was shown that the IT2 model performs better and has less conservatism in stability analysis than type-1 fuzzy model as in Li et al [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takagi-Sugeno (T-S) fuzzy system has attracted abundant researchers' attention in last decades for its extraordinary ability to approximate nonlinearity at any precision through membership function connecting linear subsystems as in Takagi and Sugeno [1], allowing existing linear system theories [2][3][4][5] to be applied to nonlinearity system analysis. The failure to tackle membership function (MF) uncertainty for type-1 fuzzy set, on the other hand, necessitates a greater focus on interval type-2 (IT2) fuzzy model, which captures uncertainties via upper and lower MFs [6][7][8][9][10][11]. It was shown that the IT2 model performs better and has less conservatism in stability analysis than type-1 fuzzy model as in Li et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…) where F i ∈ R n×s and C i ∈ R v×n are parameter matrices, 𝜔 ∈ R s is the unknown external disturbance satisfying 𝜔(k) ∈ L 2 (0, ∞), and 𝑦(k) ∈ R v is the interested output. With local fuzzy controller (10), rewrite (60) as…”
mentioning
confidence: 99%
“…In recent years, interval type-2 fuzzy sets have become a hot point for its secondary membership degree was set to 1, which simplified the type reduction procedure, and the commonly used type reduction algorithm for interval type-2 fuzzy sets was Karnik-Mendel (KM) [2] or enhanced KM (EKM) [3] algorithm. Interval type-2 fuzzy sets have been widely applied in many fields, like face recognition [4], time series prediction [5], pattern recognition [6], clustering [7], controlling systems [8][9][10][11][12][13], neuro-fuzzy systems [14], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Haghrah [16] proposed a novel Python toolkit fir interval type-2 fuzzy logic systems. Namad and Zare [35] analyzed the stability of interval type-2 control systems in frequency domain. Ontiveros-Robles et al [11] proposed a fuzzy logic controller according to performance and execution time.…”
Section: Introductionmentioning
confidence: 99%